Effects of Material Inelasticity on the Design and Performance of Reinforced Concrete Link Beams Subjected to Gravity Loading - Masri, Ferris. (2017)
Abstract: For the determination of sectional design forces in concrete structures, it is nearly always assumed that structural concrete is a linear elastic material. However, structural concrete is highly inelastic, in which the stiffness may be only a small fraction of the uncracked elastic stiffness. Codes-of-Practice provide largely empirical provisions that focus on ensuring that structural members have adequate strength, and provide little guidance to determine the performance of the structure under service loadings or overloads. Recent advancements in reinforced concrete nonlinear models and high-speed computing power provide the design engineer with the necessary tools to make a more realistic, performance-based, and optimum design. In this thesis, a case study is made of the design of six link beams of a high-rise structure that is subjected to gravity loading. An iterative design procedure is proposed and developed using VecTor2 (Vecchio et al. 2013), a specialized nonlinear finite element analysis software. VecTor2 employs constitutive relationships from various nonlinear models, including the Modified Compression Field Theory (Vecchio and Collins 1986), which defines the response of a two-dimensional continuum structure undergoing membrane action. In order to explore and validate the degree of nonlinearity in the response, a single link beam model is constructed using VecTor2 as well. The response of the single link beam model is then used to inform the iterative design procedure.; Thesis (M.S.)--Tufts University, 2017.; Submitted to the Dept. of Civil Engineering.; Advisor: Daniel Kuchma.; Committee: Masoud Sanayei, and Po-Shang Chen.; Keywords: Civil engineering, Mechanics, and Engineering.